Decoding the structural and functional diversity of GABAA receptors: from ensemble logic to therapeutic opportunities - Treviño, Mario; Guerra-Crespo, Magdalena; Padilla-Godínez, Francisco J.; Soto-Rojas, Luis O.; Manjarrez, Elías; Ortega-Robles, Emmanuel; Rodríguez-de Ita, Julieta; Arias-Carrión, Oscar (Frontiers in Pharmacology, 2025)
GABAA receptors (GABAARs) are no longer viewed as uniform inhibitory switches but as structurally diverse, dynamically regulated ensembles that decode inhibitory signals with remarkable spatial and temporal precision. Their heterogeneity arises not only from the nineteen subunit genes but also from the combinatorial logic of assembly, alternative splicing, stoichiometry, post-translational modifications, and adaptive trafficking. These ensembles function as computational modules, tuned to the demands of individual circuits where they regulate excitability, gain control, and plasticity. Here, we highlight how recent advances in cryo–electron microscopy have transformed the field, revealing unexpected conformational states, novel ligand-binding pockets, and regulatory interfaces with accessory proteins, such as NACHO. In vivo studies demonstrate that individual neurons often co-express multiple receptor subtypes, forming heterogeneous ensembles that integrate inputs from GABA, neurosteroids, histamine, endocannabinoids, and exogenous ligands. This ensemble logic reframes inhibition as a circuit-specific computation rather than a uniform force. In this review, we discuss how disorders once attributed to “too little inhibition”—including epilepsy, chronic pain, schizophrenia, and Parkinson’s disease—can now be traced to disruptions in receptor assembly, trafficking, or ensemble composition. We also examine how classical pharmacology, with benzodiazepines and barbiturates as blunt instruments, falls short of capturing this complexity. By contrast, emerging approaches—subtype-selective allosteric modulators, gene editing, chaperone manipulation, and AI-guided ligand design—point toward precision therapeutics that recalibrate inhibition at the level of specific cell types, ensembles, and circuit motifs. Taken together, inhibition emerges not as a static force but as a flexible, ensemble-driven computation embedded in receptor structure and circuit architecture, and modulated by internal states and environmental context. Decoding this logic and learning to manipulate it with precision marks the next frontier in inhibitory neuroscience and the development of next-generation therapies for brain disorders.